A history of the first Christians - Wedderburn, Alexander J. M. (London T & T Clark Int., 2005)
This work provides a survey of the history of the earliest Christian church in the period up to the fall of Jerusalem. It concentrates on: the figure of Paul; judicious and critical use of information in the Book of Acts; Judaizing versions of Christianity; and the Johannine tradition. The approach steers a middle way between an over-simplified account which fails to warn students where scholarly opinion is divided, and an in-depth academic study which attempts to document and discuss every hypothesis. Wedderburn focuses on aspects of central importance: the changing shape of church life and d.
Keywords: Church history -- Primitive and early church, ca. 30-600. RELIGION -- Christian Church -- History. RELIGION -- Christianity -- History. Church history -- Primitive and early church